ANALISIS KESULITAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL MATERI STATISTIKA BERDASARKAN TAKSONOMI BLOOM MELALUI PEMBELAJARAN DARING - Rasanti, Raras; Afrilianto, M. (IKIP Siliwangi, 2021)
This study aims to analyze the difficulties of class VIII junior high school students in working on statistical problems through online learning. The method used in this research is descriptive qualitative research method, by giving a test in the form of a description consisting of 3 questions using Bloom's taxonomic thinking ability level. The subjects in this research were students in class VIII at SMPN 6 Cimahi, totaling 17 students. The data collection technique used in this study is in the form of test results with Bloom's taxonomic ability level. low-level abilities represent C3, C4 and C5 represent moderate-level thinking skills and C6 represent high-level thinking. The results of the interpretation of the difficulties that students face in solving statistical problems are C3 got a good interpretation, C4 and C5 with less interpretation. Difficulties that affect students in solving problems on statistical material are lack of understanding of concepts, completion steps, incomplete mastery of the material, and errors in calculations. In addition, during the current pandemic, there are other non-technical obstacles such as the difficulty of accessing the internet for students living in remote areas.